PRAGMATIC EXPRESSIONS IN FRENCH LEARNING WITH THE ALTER EGO BOOK - Conny Renny Lasut; Jola C. Liuw; Jefry H. Tamboto (Journal of English Language and Literature Teaching, 2023)
Language as a verbal expression will not provide complete information in terms of humanity if it is only observed from the outside. Language as a means to express ideas, feelings and desires, has forms of expression or expressions whose meaning is not only literal. Many expressions must be interpreted according to the situation and context; thus the purpose of each expression in language communication contains pragmatic functions. Such pragmatic expressions are found in learning French with the Alter Ego book. This study applied a qualitative descriptive method using textbook data collection techniques and content analysis. The results of the study show that, in the book Alter Ego there are many pragmatic expressions that do not have a literal meaning but are socio-cultural among the speakers